Attitudes of Mothers towards the Introduction of Sex Education in Secondary Schools in Abattoir Community Jos South Local Government Area of Plateau State - Haruna, Elizabeth A.; Gorah, Kajang Y. (NIU Journal of Social Sciences, 2020)
The study was carried out to find out the Attitudes of Mothers towards the introduction of sex education in secondary schools in Abattoir community, Jos South local government area of Plateau State. The survey research was used for the study. The questionnaires administered and data collected was analyzed according to the four formulated research questions by the researcher. The population of the study was made up of the mothers who volunteered to answer the questionnaires, Abattoir community, Jos South local government area of plateau state. The instrument was given to three experts in research, two of whom are from the department of physical and health education and one tests and measurements department of the faculty of education, university of Jos, whose inputs on the instrument were very helpful. It was pretested using respondents with similar characteristics to those in the area of the main study and a reliability coefficient index of 0.78 was obtained, which was seen as a reliable figure for the instrument to be used for present study. The result of the study shows I am embarrassed when you mention sex education (2.9), my culture forbids teaching sex education (2.9), menstruation starts at puberty with different changes 205 (95.34%), and sex education encourages immorality 108(50.23%). It was concluded that low knowledge and low level of awareness on sex education, cultural beliefs of mothers towards the teaching of sex education in Abattoir community Jos south local government area of plateau state. So it was recommended among others that health educators should give health talks on sex education more frequently, programs on health should be watched, and mothers should get close to their adolescents. Health educators, mothers, both parents should take note of the above findings and utilize it well. Keywords: Attitudes, Mothers,  Sex Education and Abattoir